Esterase TriH responsible for the hydrolysis of trifloxystrobin in Hyphomicrobium sp. B1. (October 2022) - Jiang, Wankui; Zhang, Mingliang; Zhu, Qian; Wu, Chenglong; Jiang, Mingli; Ke, Zhijian; Zhou, Yidong; Qiu, Jiguo; Dong, Weiliang; Hong, Qing
Abstract: Strobilurin fungicides are widely used in rice and corn planting due to their broad-spectrum and fungal mitochondrial inhibitory activities. However, their environmental residues will cause damage to eukaryotes such as chlorella, Daphnia magna and zebrafish, etc. In this study, a bacterial strain B1 was isolated and identified as Hyphomicrobium sp., which could degrade trifloxystrobin, a representative of strobilurin fungicides. A novel esterase gene triH responsible for the trifloxystrobin detoxification and trifloxystrobin acid generation was cloned. TriH shared low identity with the reported alpha/beta-hydrolase superfamily esterases (only 26–28%). The K m and kcat values of TriH for trifloxystrobin were 2.35 ± 0.24 μM and 48.66 ± 6.43 s −1 . Also, TriH could catalyze the de-esterification reaction of azoxystrobin, picoxystrobin, and kresoxim-methyl to generate the corresponding daughter acid and methanol. Strain B1 can effectively remediate the trifloxystrobin-polluted freshwater and protect chlorella, Daphnia magna and zebrafish from the harm of trifloxystrobin. This work offers a potential strain as well as an enzyme for the remediation of strobilurin fungicides-contaminated environments. Highlights: A trifloxystrobin-degrading strain Hyphomicrobium sp. B1 was isolated. A novel esterase gene triH was cloned. TriH effectively hydrolyzes trifloxystrobin to generate trifloxystrobin-acid. Strain B1 can relieve the toxicity of trifloxystrobin to aquatic eukaryotes.